Selection of outboard motors for smaller boats - Gamarra Chinchay, Hugo Eliseo (2011)
At the present time, the country requires of the use of motors outside hut, due to the great amount of shallow-draft vessels dedicated to the recreation activity, as much fishes artisan and coastguard vessel for the lacustrine, fluvial and marine use. The study of the boats with the system of propulsion outside hut, varies between the speed and the power, thus the criterion developed for the selection of the motor and the helix must be according to the hydrodynamic results of the study of the helmet. In this project we give to the solution to the different problems from maintenance and repair that can happen in the motor outside hut taking into account criterion of reduction of costs and development of a preventive maintenance. Also, we compared advantages and disadvantages of the classic motor outside hut of 2 times as opposed to modern of the 4 times, developing differences in the lubrication systems, refrigeration, starting and others. Important also it is to see a criterion of installation and handling of the motor and different accessories that the boat requires. In conclusion in this project we set out to obtain optimal solutions for the different problems from maintenance, etc.